The awareness of Islamic retirement planning and the practice with Muslims employees in Malaysia / Mohd Shafiz Saharan...[et al.] - Saharan, Mohd Shafiz; Jamaludin, Mohd Fazil; Adzahar, Khairul Azfar; Othman, Nur Fitrah; Norddin, Nor Athirah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
This study examines the extent of Malaysians awareness on Islamic retirement planning and the predictors for the dependent variable. This study also delves into the concept of Islamic retirement planning, attitudes on investment, savings behaviour, social security and financial literacy to see the awareness issues surrounding the study of retirement. Studies have shown that Malaysians awareness on retirement planning can be considered low and only 40 percent is ready enough to retire while the rest need to retire with insufficient fund due to consumption and savings behaviour as predicted by the life-cycle theory of savings. As a country with Muslims as the dominant population, there is an urge to address this issue and to see whether or not their income and savings comply to Syariah. Data will be collected using questionnaire survey method on Muslim employees in private sectors in Malaysia. A total of 150 questionnaires will be distributed to obtain the data on the awareness of Islamic retirement planning among Muslims private employees. Data will further be analysed by the use of descriptive analysis, reliability analysis and regression analysis, and will be presented in the forms of frequency graph and table. This study expects to show the significant relationships between the independent variables which are attitudes on investment, savings behaviour, social security and financial literacy towards the awareness on Islamic retirement planning. The result is also expected to show a lower awareness of Islamic retirement planning as literatures found that most Malaysians are lacking in retirement planning. Therefore, it is important to look into extensive information regarding the level of awareness on the Islamic retirement planning so that some persistent efforts can be done in giving pre-retirement awareness program that complies to Syariah.